EZH2 regulates neuroepithelium structure and neuroblast proliferation by repressing p21. Issue 4 (April 2016) - Akizu, Naiara; García, María Alejandra; Estarás, Conchi; Fueyo, Raquel; Badosa, Carmen; de la Cruz, Xavier; Martínez-Balbás, Marian A.
Abstract : The function of EZH2 as a transcription repressor is well characterized. However, its role during vertebrate development is still poorly understood, particularly in neurogenesis. Here, we uncover the role of EZH2 in controlling the integrity of the neural tube and allowing proper progenitor proliferation. We demonstrate that knocking down the EZH2 in chick embryo neural tubes unexpectedly disrupts the neuroepithelium (NE) structure, correlating with alteration of the Rho pathway, and reduces neural progenitor proliferation. Moreover, we use transcriptional profiling and functional assays to show that EZH2-mediated repression of p21 WAF1/CIP1 contributes to both processes. Accordingly, overexpression of cytoplasmic p21 WAF1/CIP1 induces NE structural alterations and p21 WAF1/CIP1 suppression rescues proliferation defects and partially compensates for the structural alterations and the Rho activity. Overall, our findings describe a new role of EZH2 in controlling the NE integrity in the neural tube to allow proper progenitor proliferation.